O protagonismo das seno têrenoe: Mulheres Terena - Sebastião, Lindomar Lili (2019)
The work, written by a native Terena, aims to present the research titled The progeny of the sine Têrenoe - women Terena. The thesis presents the analysis of the protagonism of indigenous women of the Terena ethnic group in the State of Mato Grosso do Sul. In this work, I use the qualitative methodology, especially ethnography, oral history and participant observation to collect fundamental data in the construction of the thesis . Considering in this work, the women acting in the decision-making processes of the community, of great influence in the domestic group. Nowadays, women have surpassed this political space, conquering new activities and new roles reinforced by the education (formation) added by the indigenous movement and the processes of territorial reoccupation. In a sense, the cultural re-significances contributed to the Terena appropriating new knowledge by taking them as a mechanism for dialogue, mediation and demand of their constitutional rights to the State, especially the demarcation of their lands, a space where women Terena took control contributing to leave the private context and enter the public space as protagonists of their stories